THE EFFECTIVENESS OF CLUSTERING TECHNIQUE IN IMPROVING STUDENTS’ WRITING SKILL IN NARRATIVE TEXT AT SMA NEGERI 21 MAKASSAR - Suci Ma'alikul Mulky Haris; Nur Qalbi; Herlina Daddi (FKIP Unismuh Makassar, 2022)
This research aims to find out The Effectiveness of Clustering Technique in Improving Students’ Writing Skill In Narrative Text. This research was conducted at SMA Negeri 21 Makassar. The design of this research is Pre-Experimental Design. The population of this study was the first-grade students in academic years 2020/2021 in SMAN 21 Makassar, which was selected by using cluster random sampling technique, while the sample of this study was 30 students. The instrument of this study was a test that used pre-test and post-test.The mean score of the pre-test in content 71,1 was lower than post-test 80,6. From the t-test, the study found that the value of t-test in generic structure pre-test 20,62 was fair than t-table 1.538, and the value of t-test in generic structure post-test 38,71 was greater than t-table 1.538. There was a difference between the students’ writing before and after applying the clustering technique in the class. It shows that the Null Hypothesis (H0) was rejected and the alternative hypothesis (H1) was accepted. The result of the data shows that writing in terms of the generic structure of narrative text through the clustering technique was a fairly effective method to improving students' writing skills in narrative text.